New Civilization in the Post-Covid-19 Health World & Lesson Learned from the Netherlands - Armyn Nurdin; Tjay Tan; Isti Ilmiati Fujiati (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2020)
New Civilizations in the Post-Covid-19 World Health There  are  several  possibilities  that  will happen  after  the Covid-19  outbreak  ends.  This  is  the  other  side  of  the Covid-19 pandemic.  There  is  a  term  called  see  the  un- seen, or seeing something before it happens. An illustrative example is that everyone sees the apple falling down, but only one person sees why or what causes the apple to fall down. This  is  Isaac  Newton.  Based  on  this phenomenon, the formula for the gravitational force or the gravitational force of the earth is triggered. This paper focuses on what might happen in the future.Indeed, the earth repairs itself in its own way, and that is for the benefit of mankind. The Covid-19 outbreak that is currently happening is a very positive thing for human life. Under the earth there are shifts in the earth’s plates which cause tectonic earthquakes. What is the goal? The aim is to stabilize the earth so that an asteroid collision does not occur. There is a plague on earth, what does it mean? Its meaning is  to  improve  human  life.  So,  let’s interpret  the  current outbreak as something positive. Previously in Europe, there were millions of deaths due to PES disease. At that time, most farmers died, so the land owners were short of labor. What is the meaning? First, farmers have a high bargaining position. Second, after the plague occurred, then there was the collapse of feudalism. In the past, peasants worked in a kind of forced labor. Then the modern economic system was  born.  It was  started  at  that  time  when  farmers  were paid in cash which had never happened before. This was the beginning of the growth of the modern economic system2.